Análise de alguns elementos essenciais para a gestão de relacionamento: um estudo de caso - Alecrim-Santos, Carlos Alberto (2003)
The great majority of the CRM projects have valued the technological aspects and, at the same time, they have imposed to a second leveI individuaIs, company culture and organizational environrnent. The latter was not considered important to the enlargement and strategic accomplishment that determine a successful organization. Nowadays, new subjects are modifying the above mentioned environrnent. Consequently, it is important to analyze and identify those aspects that help to build a successful company in the society. This study focuses on the main aspects for the implementation of Relationship Management under these new purposes which will bring a significant instrument to a better understanding of the current situation in several Brazilian organizations. The methodology of this research is exploratory and the data collected through interviews with main partners based on their everyday dealings with their customers. This methodology works with interviews, completed forms and following the Likert grade. The final results identify the best solutions found by the focused organizations to solve their problems mainly based on human capital and their qualifications. The research is enriched by a case study on a Brazilian private bank, which is experiencing a process of CRM implementation.